Primes in the form of P 4k2+1. - Iquiña, Patrick Just (Iloilo City UPHSI, 2005)
This paper studied the primes in the form of P = 4k^2 + 1 and determined its properties and the patterns associated with it. It was found that (1) if k > 1, then k cannot be congruent to +/- 1 mod 5; (2) if k > 1, P is only congruent to 1 or 7 mod 10; (3) there exists consecutive k which will make P prime; (4) k cannot be congruent to +/- 4 mod 13; and (5) if k =/, then k cannot be congruent to +/- 2 mod 17.
Research II : Research Manuscripts
Keywords: Primes